2009
DOI: 10.3402/gha.v2i0.1985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of physical inactivity in nine rural INDEPTH Health and Demographic Surveillance Systems in five Asian countries

Abstract: Background Physical inactivity leads to higher morbidity and mortality from chronic non-communicable diseases (NCDs) such as stroke and heart disease. In high income countries, studies have measured the population level of physical activity, but comparable data are lacking from most low and middle-income countries.Objective To assess the level of physical inactivity and its associated factors in selected rural sites in five Asian countries.Methods The multi-site cross-sectional study was conducted in nine rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
68
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 18 publications
23
68
3
1
Order By: Relevance
“…retirement, have on physical activity in Oman (26). The Omani adult population was found to be least active in the leisure domain compared with the transport and work domains, a similar pattern seen in other developing countries (27,28). In the coming years it is likely that work activity will decrease and may not be replaced with active transport and leisure, a trend seen in both developed and developing countries (29).…”
mentioning
confidence: 64%
“…retirement, have on physical activity in Oman (26). The Omani adult population was found to be least active in the leisure domain compared with the transport and work domains, a similar pattern seen in other developing countries (27,28). In the coming years it is likely that work activity will decrease and may not be replaced with active transport and leisure, a trend seen in both developed and developing countries (29).…”
mentioning
confidence: 64%
“…During the period 1986-2006, estimated chronic diseaserelated mortality increased from 8% to 68%, whereas estimated communicable disease mortality dropped from 52% to 11% in a part of rural Bangladesh 8) . This epidemiological transition toward a higher chronic disease burden, particularly by CVD, is occurring most likely as a consequence of rapid urbanization 2,4,[10][11][12] , change in dietary habits and lifestyle 2,4,11,13,14) , popularity of fast food items and beverages 4,15) , rising consumption of tobacco 4,11,16) , increase in buying capacity 1,15) , decrease in the levels of physical activity 2,4,14,[16][17][18] , successful immunization programs against childhood infectious disease 9) , and concomitant decline of infec-In this paper, we have used the term "cardiovascular diseases (CVD)" according to the definitions of Global Burden of Disease (GBD) cause categories in terms of International Classification of Diseases, Tenth Revision (ICD-10) codes 20) . Here CVD includes the following: 1) rheumatic heart disease (ICD-10 code: I01-I09), 2) hypertensive heart disease (ICD-10 code: I10-I13), 3) ischemic heart disease (ICD-10 code: I20-I25), 4) cerebrovascular disease (ICD-10 code: I60-I69), 5) inflammatory heart diseases (ICD-10 code: I30-I33, I38, I40, I42), and 6) other cardiovascular diseases (ICD-10 code: I00, I26-I28, I34-I37, I44-I51, I70-I99) 20) .…”
Section: Introductionmentioning
confidence: 99%
“…However, with occupations becoming less labour-intensive with the advent of mechanization, individuals will now have to derive most of their physical activity from LTPA. The few studies on LTPA from India have reported that only a low proportion of individuals (ranging from 3 to 15%) are physically active in their leisure time [9][10][11]. This implies that overall physical activity levels in India are likely to decline precipitously in the future, setting the stage for acceleration in the incidence of NCDs.…”
Section: Introductionmentioning
confidence: 99%